The role of information technology in legal education - Akhmetov, A.S. (Publ.KarSU, 2017)
In thе article, the comparative analysis of scientific research of domestic and foreign authors on the application of digital educational resources in the preparation of future lawyers. Much attention is paid in the article to the use in the educational process of information resources, in which educational material can be presented in digital (electronic) format. In the opinion of the author, the development of information and communication technologies by university teachers, as well as the widespread use of digital educational resources to create teaching and methodological support will improve the quality of legal education. Competent use of information technology increases the pedagogical impact on the formation of the creative potential of students, increases the level of scientific culture. In conclusion, the author comes to the conclusion that today there is a need to create a unified approach that reveals the didactic possibilities of using digital educational resources (DERs) containing a system of standards in the creation and implementation of electronic resources products in the educational process.
Заң білім берудегі ақпараттық технологиялардың рөлі
Роль информационных технологий в юридическом образовании
Keywords: education; system; digital electronic resource; information environment; science; education standards; electronic format; virtual environment; internet; remote technology